36=9(f-90)

Simple and best practice solution for 36=9(f-90) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36=9(f-90) equation:



36=9(f-90)
We move all terms to the left:
36-(9(f-90))=0
We calculate terms in parentheses: -(9(f-90)), so:
9(f-90)
We multiply parentheses
9f-810
Back to the equation:
-(9f-810)
We get rid of parentheses
-9f+810+36=0
We add all the numbers together, and all the variables
-9f+846=0
We move all terms containing f to the left, all other terms to the right
-9f=-846
f=-846/-9
f=+94

See similar equations:

| 2(3a+5)=4a+6 | | 88=8(w-81) | | 28=9y-17 | | 8m+42=8m+6 | | 4=(3x+1)-11 | | 1=c/6-3 | | 123+(x)=189 | | p-64/2=10 | | 3x +2= x −2 | | 20+y=9 | | -3+5(1+m)=6+2m | | 72=8(y+4) | | 134+84+68+(x)=360 | | 17x+8=7x+4 | | -6(2+7n)=38+8 | | 73+158+51+(x)=360 | | -9b-4=2b+7 | | 0.666666666x-5=1 | | 4-2×=6x-5 | | (9x-73)+(3x+19)=90 | | 32x+7=12x+2 | | -8m-1=15 | | 4-2x=6x-5 | | 7-9x=12-10x | | 6k-8=4 | | x^2-6x-12-51=0 | | 24u-30-25u+25=-60 | | 4c+2=10;c=2 | | 9x9=8x | | 2x+7=5x+7 | | 14(2-x)=14(4) | | 8n-3=5n-12 |

Equations solver categories